PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO PADA MATERI TEKNIK DASAR PASSING BOLA VOLI DI MTS AR-RAHMAN PALEMBANG - Wijaya, Azhar Hanif (Jurnal Keolahragaan JUARA, 2021)
Research methods can be classified based on the purpose and level of naturalness of the object under study. The type of this research is Research and Development. "The research and development method is the result of research and discussion, it was found that the results of trials in small groups obtained that 3 students (60%) had good responses, and 2 students (40%) gave very good responses. It can be concluded that the development of video-based learning media on the basic techniques of passing volleyball in class VIII MTs Ar-Rahman SMA is categorized as good and feasible to be used as learning media.